553 Quality Improvement: The Implementation of Routine Tertiary Trauma Survey in all Trauma Patients Aged Over 60 Years in a Busy District General Hospital. (4th May 2021) - Hughes, C; Berry, A
Abstract: Introduction: Missed injury (MI) in trauma-patients is a widely reported phenomenon, with rates varying from 1.9-39%. Methods exist to reduce the incidence of MI's such as the tertiary-trauma-survey (TTS). Robust primary and secondary surveys should indeed identify all injuries and facilitate management. However, for trauma patients, there remains an unwanted prevalence of MI. We hypothesized the addition of TTS may reduce the incidence of MI in a District General Hospital (DGH) and reduce associated morbidity and mortality; in particular in those aged >60. Method: Patient notes for 18 consecutive trauma admissions in those >60 years were audited for admission demographics, timing and outcome of primary, secondary, and tertiary surveys, and occult injury. The TTS bundle was subsequently implemented in all trauma inpatients >60. Results: In the primary round, 11% (n = 2) had evidence of TTS within 36hr of admission, reflective of exceeding the TARN criterion. TTS is now being utilised and we expect to see >98% compliance. Conclusions: TTS is now incorporated as routine patient care for all trauma admissions >60. Compliance will be re-audited; aiming to reduce the opportunity for missed injury morbidity.